PENGGUNAAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN SIFAT-SIFAT CAHAYA DI SEKOLAH DASAR - RESTUTI, RESTUTI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The use of concrete objects in Media Properties Increased Light Learning in Primary Schools. This study aims to describe the use of media in enhancing learning concrete objects, obstacles and solutions use. Subject of this study, fifth grade students at SDN 1 Kedungpuji number of 16 students. The experiment was conducted three cycles, each cycle consisting of planning, action, observation, and reflection. Data collection techniques used observation, analysis of student work, tests, and questionnaires. The validity of the data using triangulation techniques. Analysis of data using qualitative and quantitative analysis. The result can enhance learning properties of light elementary fifth grade students, the learning process and learning outcomes reached 90.5 reached 86. Keywords: Concrete Media Objects, Learning, Qualities of Light Abstrak: Penggunaan Media Benda Konkret dalam Peningkatan Pembelajaran Sifat-Sifat Cahaya di Sekolah Dasar. Penelitian ini bertujuan mendeskripsikan penggunaan media benda konkret dalam meningkatkan pembelajaran, menemukan kendala dan solusi penggunaannya. Subjek penelitian ini, siswa kelas V SDN 1 Kedungpuji sejumlah 16 siswa. Penelitian dilaksanakan tiga siklus, tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Teknik pengumpulan data menggunakan observasi, analisis kerja murid, tes, dan angket. Validitas data menggunakan teknik triangulasi. Analisis data menggunakan analisis kualitatif dan kuantitatif. Hasilnya dapat meningkatkan pembelajaran sifat-sifat cahaya siswa kelas V SD, proses pembelajaran mencapai 90,5 dan hasil belajar mencapai 86.   Kata kunci: Media Benda Konkret, Pembelajaran, Sifat-Sifat Cahaya.